Utilization of Sengon Wood Ash for Soil Stabilization and Its Impact on Unsoaked CBR Value - Fathonah, Woelandari; Mina, Enden; Kusuma, Rama Indera; Ramdani, Fahreza (Jurnal Teknologi, 2024)
Soil is one of the critical factors influencing construction robustness. The land situated in Cibingbin Village, Cibaliung District, Pandeglang Regency, falls under the category of soil with low bearing capacity. Therefore, the soil in this area requires stabilization to enhance its load-bearing capacity. The field's CBR value, determined through DCP testing, was found to be 2.67%. The target CBR value for subgrade suitability is 6%, indicating the necessity for soil stabilization at this location. This study aims to assess the physical characteristics of the native soil and its CBR value after stabilization using sengon wood ash. Various percentages of sengon wood ash, namely 4%, 6%, 8%, 10%, and 12%, were utilized with curing periods of 0 and 3 days. Soil classification was performed using the USCS method, and the CBR test conducted was the unsoaked CBR test. The results revealed that the addition of 4% sengon wood ash, with a 3-day curing period, yielded an optimum CBR value of 7%. Sengon wood waste ash proved effective in increasing the CBR value. Furthermore, the use of sengon wood ash did not significantly reduce the plasticity index (PI) value. After stabilization with sengon wood ash, the PI value remained at 35.685%, categorizing it as highly plastic. Additional research is recommended to address the limitations of sengon wood ash and achieve a significant reduction in the PI value to meet the subgrade criteria